1998
DOI: 10.1097/00005392-199810000-00027
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Post-Radical Prostatectomy Incontinence and Correlation of Symptoms With Urodynamic Findings

Abstract: Incontinence after radical prostatectomy is associated with intrinsic sphincter deficiency in the overwhelming majority of patients. Bladder dysfunction rarely is an isolated cause. When present on urodynamic tests bladder dysfunction may not always be a significant contributor to incontinence. The symptom of stress urinary incontinence (or its absence) accurately predicts the finding (or absence) of intrinsic sphincter deficiency on urodynamics. Urge incontinence is not as reliable in predicting incontinence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 14 publications
2
72
0
2
Order By: Relevance
“…In a post-prostatectomy population one study reports clinical history to be 1.00 sensitive and 0.50 specific for diagnosing USI and 0.50 sensitive and 0.77 specific for diagnosing DO. 168 One study reports a sensitivity of 0.73 and specificity of 0.60 for the diagnosis of DO by clinical history 169 and one study reports a higher incidence of urge symptoms in a urodynamically confirmed DO group compared with a urodynamically normal group.…”
Section: Diagnosis Of Do and Usi In Menmentioning
confidence: 99%
“…In a post-prostatectomy population one study reports clinical history to be 1.00 sensitive and 0.50 specific for diagnosing USI and 0.50 sensitive and 0.77 specific for diagnosing DO. 168 One study reports a sensitivity of 0.73 and specificity of 0.60 for the diagnosis of DO by clinical history 169 and one study reports a higher incidence of urge symptoms in a urodynamically confirmed DO group compared with a urodynamically normal group.…”
Section: Diagnosis Of Do and Usi In Menmentioning
confidence: 99%
“…Broadly, these include detrusor over-and underactivity, decreased vesical compliance, ISD, and bladder outlet obstruction, as in the case of anastomotic strictures. [16,50] The presence of these factors pre-operatively must also be considered. Most cases of incontinence are a result of intraoperative damage to the native urinary sphincteric mechanisms [11] , particularly the intrinsic sphincter component.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Most cases of incontinence are a result of intraoperative damage to the native urinary sphincteric mechanisms [11] , particularly the intrinsic sphincter component. [16,50,51] Bladder denervation during prostatectomy is also a frequent cause of incontinence after the operation, resulting in impaired detrusor contractility and poor bladder compliance.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The UI rate after RP remains high even with the advances in the surgical technique and technology. UI after RP is primarily SUI related to ISD [48][49][50] but bladder dysfunction after such a major pelvic surgery was also found to have a role [51][52][53]. Examples of bladder dysfunction after RP include DO, low bladder compliance, impaired detrusor contractility, or changed bladder sensation.…”
Section: Voiding Dysfunction After Rpmentioning
confidence: 99%